The effects of smoking on athletic performance: A systematic literature review - Adrian, Muhammad Bayu; Yosika, Ghana Firsta; B, Putra Sastaman (Universitas Tanjungpura, 2026)
Background The link between smoking and athletic performance is important to consider, as many people who exercise still smoke. Smoking is thought to negatively impact health, while exercise requires optimal health and performance. Objectives This study aims to review the scientific literature regarding the relationship between smoking and sports performance. Methods A systematic literature review was conducted using the PubMed database following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The keyword “Smoking and Sports Performance” was used to identify relevant studies. Articles published between 2020 and 2025 that discussed smoking and sports performance were screened according to predetermined inclusion and exclusion criteria. A total of 15 articles met the eligibility criteria and were included in the review. Results The reviewed studies consistently showed that smoking negatively affects sports performance and physical fitness. Smokers demonstrated lower aerobic capacity (VO₂max), reduced cardiorespiratory fitness, decreased lung function, higher heart rates, slower recovery processes, and poorer physical fitness compared with non-smokers. Several studies also reported increased risks of hypertension, impaired cognitive function, and accelerated biological aging among smokers. Conversely, smoking cessation was associated with improvements in aerobic capacity, cardiovascular health, and overall physical fitness. Conclusion Smoking has a significant negative impact on sports performance and athlete health. The evidence indicates that avoiding or quitting smoking can improve physical fitness, aerobic capacity, and recovery, thereby supporting better athletic performance.